Implementação do modelo ULM na plataforma ATP para o estudo de transitórios em linhas de transmissão aéreas com configuração assimétrica - Felipe de Oliveira Silva Zanon (2019)
This dissertation investigates the simulation of transients in asymmetrical overhead line configurations considering the Universal Line Model (ULM) and a more rigorous modeling of the ground effect in the calculation of the line parameters per unit length. The ULM is indicated to simulate lines with asymmetric configuration because it is developed directly in the phase domain. This model is recognized for its accuracy and generality, and it is currently adopted as a reference for electromagnetic transient studies. Since this model is only implemented on commercial electromagnetic transients programs, it was decided to implement it in the Alternative Transients Program (ATP), which is free. This was performed by implementing a fitting routine in MATLAB and by using a strategy based on the foreign models tool available in ATP. The performed analyses indicate the validity of the ULM implementation in ATP, and show that models implemented in commercial platforms are not always entirely reliable or rigorous, which demonstrates the need for full control in all stages involved in the model implementation. It was also confirmed that the JMarti transmission line model is not suitable for simulating transients on asymmetrical overhead line configurations. Regarding the use of more rigorous ground modeling, it is concluded that it is possible to assume a constant parameter soil and to calculate the ground return impedance considering the Deri or Carson approximations only for low-resistivity soils. For high-resistivity soils, it is recommended to consider the variation of the soil parameters with frequency and to use more rigorous expressions for the calculation of the ground return impedance and the ground admittance.